“MENJADI KOREA”: MELIHAT CARA, BENTUK DAN MAKNA BUDAYA POP KAREA BAGI REMAJA DI SURABAYA - Sarah Fella; Abdus Sair (Universitas Wijaya Kusuma Surabaya, 2021)
This article explores the ways, forms and meanings of Korean pop culture for teenagers in Surabaya. Several studies show that Korean pop culture has developed in Indonesia since the early 2000s through Korean films, followed by music, food and beauty products. However, studies that focus on the ways, forms and meanings of Korean pop culture for Surabaya youth in metropolitan city are still very limited. This article, on the other hand, wants to discuss this in field research through in-depth interviews with 5 Surabaya teenagers, members of KLOSS (Korea Lovers Surabaya Community). This article shows that Korean pop culture has become a new culture for youth in Surabaya because its novelty values. They get the Korean pop through television and social media. The prominent forms of pop culture used by the majority of youths are Korean cultural symbols represented in everyday life. Meanwhile, the meaning of Korean pop culture is in the form of information about Korean youth, Korean artists and other “Korean-ness”.Keywords: Korean Pop Culture, To be Korea, Korean-ness, Surabaya Teenagers.